Worker satisfaction with adaptive automation and working conditions: a theoretical model and questionnaire as an assessment tool. Issue 4 (2nd October 2021) - Villani, Valeria; Sabattini, Lorenzo; Żołnierczyk-Zreda, Dorota; Mockałło, Zofia; Barańska, Paulina; Fantuzzi, Cesare
Abstract : This article focuses on methods and tools to measure worker satisfaction with reference to industrial automation. Despite technological advances in automation, the role of human workers on industrial shop floors remains crucial. To promote humans' roles, production systems should be designed and organized so workers are valued and get satisfactory jobs. The article presents a novel holistic model of worker satisfaction with adaptive automation and working conditions. The model takes into account psychosocial and physical working conditions and the characteristics of the automation system the worker interacts with and its user interface. We propose a questionnaire to be used as a practical tool to assess worker satisfaction with industrial automation, considering also the case of adaptive automation. The proposed version of the questionnaire is the result of pilot testing carried out among shop floor operators and takes into account adjustments derived from end-user feedback.